Transcription Factors in Fungi: TFome Dynamics, Three Major Families, and Dual-Specificity TFs - Shelest, Ekaterina (Frontiers in Genetics, 2017)
Transcription factors (TFs) are essential regulators of gene expression in a cell; the entire repertoire of TFs (TFome) of a species reflects its regulatory potential and the evolutionary history of the regulatory mechanisms. In this work, I give an overview of fungal TFs, analyze TFome dynamics, and discuss TF families and types of particular interest. Whole-genome annotation of TFs in more than 200 fungal species revealed ~80 families of TFs that are typically found in fungi. Almost half of the considered genomes belonged to basidiomycetes and zygomycetes, which have been underrepresented in earlier annotations due to dearth of sequenced genomes. The TFomes were analyzed in terms of expansion strategies genome- and lineage-wise. Generally, TFomes are known to correlate with genome size; but what happens to particular families when a TFome is expanding? By dissecting TFomes into single families and estimating the impact of each of them, I show that in fungi the TFome increment is largely limited to three families (C6 Zn clusters, C2H2-like Zn fingers, and homeodomain-like). To see whether this is a fungal peculiarity or a ubiquitous eukaryotic feature, I also analyzed metazoan TFomes, where I observed a similar trend (limited number of TFome-shaping families) but also some important differences connected mostly with the increased complexity in animals. The expansion strategies of TF families are lineage-specific; I demonstrate how the patterns of the TF families’ distributions, designated as “TF signatures”, can be used as a taxonomic feature, e.g., for allocation of uncertain phyla. In addition, both fungal and metazoan genomes contain an intriguing type of TFs. While usually TFs have a single DNA-binding domain, these TFs possess two (or more) different DNA-binding specificities. I demonstrate that dual-specific TFs comprising various combinations of all major TF families are a typical feature of fungal and animal genomes and have an interesting evolutionary history involving gene duplications and domain losses.